Assessing European Wheat Sensitivities to Parastagonospora nodorum Necrotrophic Effectors and Fine-Mapping the Snn3-B1 Locus Conferring Sensitivity to the Effector SnTox3 - Downie, Rowena C.; Bouvet, Laura; Furuki, Eiko; Gosman, Nick; Gardner, Keith A.; Mackay, Ian J.; Campos Mantello, Camila; Mellers, Greg; Phan, Huyen T. T.; Rose, Gemma A.; Tan, Kar-Chun; Oliver, Richard P.; et al. (Frontiers in Plant Science, 2018)
Parastagonospora nodorum is a necrotrophic fungal pathogen of wheat (Triticum aestivum L.), one of the world’s most important crops. P. nodorum mediates host cell death using proteinaceous necrotrophic effectors, presumably liberating nutrients that allow the infection process to continue. The identification of pathogen effectors has allowed host genetic resistance mechanisms to be separated into their constituent parts. In P. nodorum, three proteinaceous effectors have been cloned: SnToxA, SnTox1 and SnTox3. Here, we survey sensitivity to all three effectors in a panel of 480 European wheat varieties, and fine map the wheat SnTox3 sensitivity locus Snn3-B1 using genome wide association scans (GWAS) and an eight-founder wheat multi-parent advanced generation inter-cross (MAGIC) population. Using a Bonferroni corrected P≤0.05 significance threshold, GWAS identified ten significant markers defining a single locus, Snn3-B1, located on the short arm of chromosome 5B explaining 32% of the phenotypic variation (peak SNPs, Excalibur_c47452_183 and GENE-3324_338, -log10P=20.44). Single marker analysis of SnTox3 sensitivity in the MAGIC population located Snn3-B1 via five significant SNPs, defining a 6.2 kb region that included the two peak SNPs identified in the association mapping panel. Accordingly, SNP Excalibur_c47452_183 was converted to the KASP genotyping system, and validated by screening a subset of 95 wheat varieties, providing a valuable resource for marker assisted breeding and for further genetic investigation. In addition, composite interval mapping in the MAGIC population identified six minor SnTox3 sensitivity QTL, on chromosomes 2A (QTox3.niab-2A.1, P-value = 9.17-7), 2B (QTox3.niab-2B.1, P=0.018), 3B (QTox3.niab-3B.1, P=48.51-4), 4D (QTox3.niab-4D.1, P=0.028), 6A (QTox3.niab-6A.1, P=8.51-4) and 7B (QTox3.niab-7B.1, P=0.020), each accounting for between 3.1 and 6.0 % of the phenotypic variance. Collectively, the resources generated here provide breeders with knowledge and resources regarding the sensitivity of European wheat germplasm to P. nodorum effectors, as well as simple diagnostic markers for determining allelic state at Snn3-B1.